Towards a more flexible approach to the fraud exception in letters of credit under South African law: a comparative analysis with select common law approaches and the UNCITRAL Convention - Ngoma, Wilson (Department of Commercial Law, 2015)
The aim of this dissertation is to recommend an alternative approach to the fraud exception in South African law. The Current South African position as with the English law, places more weight on upholding the sanctity of the autonomy principle in letters of credit than preventing fraud. This is mainly because the courts have traditionally taken the view that protection of the autonomy principle is central to promoting the needs of trade and maintaining the integrity of the international banking community. Hence, this dissertation argues that an approach to the fraud exception in South African law that is more in line with that of the American law and/or the UNCITRAL Convention strikes a better balance in upholding the value of letters of credit and combatting fraud than the current South African position. Based on the comparative analysis of the position in the United Kingdom, United States of America and under the UNCITRAL Convention, the dissertation seeks to draw upon important lessons and principles pivotal to a preferable approach to the fraud exception in South African law that would enhance a better balance between the autonomy arguments and deterrence of fraud.